2016
DOI: 10.3926/jiem.2086
|View full text |Cite
|
Sign up to set email alerts
|

Application of the TDABC model in the logistics process using different capacity cost rates

Abstract: Abstract:Purpose: The understanding of logistics process in terms of costs and profitability is a complex task and there is a need of more research and applied work on these issues. In this research project, the concepts underlying Time-Driven Activity Based Costing (TDABC) have been used in the context of logistics costs.Design/methodology/approach: A Distribution Centre of wood and carpentry related materials has been studied. A multidisciplinary team has been composed to support the project including the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
(24 reference statements)
0
14
0
2
Order By: Relevance
“…To address the problems associated with the implementation and operation of the conventional ABC system, Kaplan and Anderson (2007) introduced the concept of TDABC. The approach uses time duration as the single cost driver and this easies its application in changing business environments (Afonso & Santana, 2016). Duration drivers estimate the time required to perform a task.…”
Section: Time‐driven Activity‐based Costingmentioning
confidence: 99%
“…To address the problems associated with the implementation and operation of the conventional ABC system, Kaplan and Anderson (2007) introduced the concept of TDABC. The approach uses time duration as the single cost driver and this easies its application in changing business environments (Afonso & Santana, 2016). Duration drivers estimate the time required to perform a task.…”
Section: Time‐driven Activity‐based Costingmentioning
confidence: 99%
“…Under this criterion, it could be stated that the transport system (TS) constitutes the set of modes, means and facilities or infrastructure, which serve as a material basis for the execution, by man, of transportation activities, through the economic and juridical relationships established in an organization (Lee & Lam, 2012;Afonso & Santana, 2016;Movahedipour et al, 2016;Mimouni & Abouabdellah, 2016;Martínez-Vivar et al, 2016). In the previous approach the elements that compose this system materialized in the material base and the economic and legal relations.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…On the other hand, logistics involves four subsystems recognized in the literature, among which are listed: Procurement, production, distribution and reuse, which in their holistic operation contribute to the performance of the business system (Chang & Lin, 2016;Ayala Bécquer et al, 2001;Ballou, 1991;Altendorfer & Zsifkovits, 2016;Fahimnia et al, 2013;Chase et al, 2009;Swink et al, 2014;Heizer & Render, 2009;Krajewski, 2012;Magee, 1968;Carrasco et al, 2017;Stoner, 1996;Raza et al, 2017;Cespón-Castro & Auxiliadora-Amador, 2003;Vélez, 1996;Lee & Lam, 2012;Afonso & Santana, 2016;Movahedipour et al, 2016;Mimouni, & Abouabdellah, 2016;Martínez-Vivar et al, 2016).…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In case of cost variation in the health care, Haas and Kaplan (2017) found that TDABC still provided accurate estimation in care cycle cost. Afonso and Santana (2016) presented a cost model using TDABC associated with multiple time equations and discussed the profitability at different cost objects. Yu et al (2016) found that TDABC resulted in precise cost and identified inefficiencies in health care.…”
mentioning
confidence: 99%